Combined cord blood and bone marrow transplantation from the same human leucocyte antigen‐identical sibling donor for children with malignant and non‐malignant diseases. (18th December 2014) - Tucunduva, Luciana; Volt, Fernanda; Cunha, Renato; Locatelli, Franco; Zecca, Marco; Yesilipek, Akif; Caniglia, Maurizio; Güngör, Tayfun; Aksoylar, Serap; Fagioli, Franca; Bertrand, Yves; Addari, Maria Carmen; et al.
Summary: Umbilical cord blood (UCB) from an human leucocyte antigen (HLA)‐identical sibling can be used for transplantation of patients with malignant and non‐malignant diseases. However, the low cellular content of most UCB units represents a limitation to this approach. An option to increase cell dose is to harvest bone marrow (BM) cells from the same donor and infuse them along with the UCB. We studied 156 children who received such a combined graft between 1992 and 2011. Median age was 7 years and 78% of patients ( n  = 122) were transplanted for non‐malignant diseases, mainly haemoglobinopathies. Acute leukaemia ( n  = 26) was the most frequent malignant diagnosis. Most patients (91%) received myeloablative conditioning. Median donor age was 1·7 years, median infused nucleated cell dose was 24·4 × 10 7 /kg and median follow‐up was 41 months. Sixty‐days neutrophil recovery occurred in 96% of patients at a median of 17 d. The probabilities of grade‐II‐IV acute and chronic graft‐ versus ‐host disease (GVHD) were 19% and 10%, respectively. Four‐year overall survival was 90% (68% malignant; 97% non‐malignant diseases) with 3% probability of death. In conclusion, combined UCB and BM transplantation from an HLA‐identical sibling donor is an effective treatment for children with malignant and non‐malignant disorders with high overall survival and low incidence of GVHD.